Analysis of transformations of the modern economy - Pidlisna, Olena; Duchenko, Maryna (Technology audit and production reserves, 2023)
The object of research is the economy, its types and directions of modern transformation in the conditions of global instability of world development in the 21st century. Since the economy is a reflection of the trends of social development, the understanding of the definition of «modern economy» changes and needs clarification and improvement. The active movement of resources and capacities as a result of global social upheavals of the 21st century has created a need to understand aspects of the migration economy. The research is analytical. During the research, special methods of information processing and analysis were used: elimination, intuitive method. The work is aimed at the systematization and generalization of the terminology used to characterize modern social production processes, determining the expediency of introducing the definition «migration economy». This will make it possible to formalize the process of making management decisions in the conditions of the trend of total migrations. The paper analyzes the terms that describe the economy at the current stage of development. It is shown that several terms are used simultaneously: «movement», «migration», «relocation». And only the term «migration» has an essential interpretation as emergency and unplanned actions. An attempt was made to formulate the definition of «migration economy» as a specific economic activity of society, caused by both voluntary and forced (including emergency) migration of subjects of economic relations across national or regional borders, which changes the spectrum of economic, social interactions and the economic landscape both in the territories of departure and in the territories of destination. The work shows that the real processes of the world economy require a modern terminological definition. This will form the basis for its forecasting and development. The interpretation of the modern economy as a migration economy allows for the formulation of new principles of the organization of production processes: autonomy, adaptability, allocation of business blocks according to the principle of optimal added value. The practical value of the work lies in the effort to form a definition of the modern economy, which makes it possible to specify management decisions on the organization of production and to understand the directions of changes.